HIV-1-Specific CD11c+ CD8+ T Cells Display Low PD-1 Expression and Strong Anti-HIV-1 Activity - Guo, An-Liang; Zhao, Jin-Fang; Gao, Lin; Huang, Hui-Huang; Zhang, Ji-Yuan; Zhang, Chao; Song, Jin-Wen; Xu, Ruo-Nan; Fan, Xing; Shi, Ming; Jiao, Yan-Mei; Wang, Fu-Sheng (Frontiers in Immunology, 2021)
Exhaustion of HIV-1-specific CD8+ T cells prevents optimal control of HIV-1 infection. Identifying unconventional CD8+ T cell subsets to effectively control HIV-1 replication is vital. In this study, the role of CD11c+ CD8+ T cells during HIV-1 infection was evaluated. The frequencies of CD11c+ CD8+ T cells significantly increased and were negatively correlated with viral load in HIV-1-infected treatment-naïve patients. HIV-1-specific cells were enriched more in CD11c+ CD8+ T cells than in CD11c- CD8+ T cells, which could be induced by HIV-1-derived overlapping peptides, marking an HIV-1-specific CD8+ T cell population. This subset expressed higher levels of activating markers (CD38 and HLA-DR), cytotoxic markers (granzyme B, perforin, and CD107a), and cytokines (IL-2 and TNF-α), with lower levels of PD-1 compared to the CD11c- CD8+ T cell subset. In vitro analysis verified that CD11c+ CD8+ T cells displayed a stronger HIV-1-specific killing capacity than the CD11c- counterparts. These findings indicate that CD11c+ CD8+ T cells have potent immunotherapeutic efficacy in controlling HIV-1 infection.